In Vitro Evaluation of Binding of Fish Mucus by Nanoparticles Induced Oxidative Stress on the Common Carp - Zulfqar Ahmad; Muhammad Liaqat; Muhammad Naeem ul Hassan; Muhammad Masood; Muhammad Irfan Haider Jafri; Azmat Ullah; Hashmat Riaz; Muhammad Sikandar (Central Asian Journal of Medical and Natural Science, 2022)
Common carp (Cyprinus carpio) is a large, deep bodied fish and can tolerate all types of water. Fish skin mucus comprises numerous immune substances that provide defense against a wide spectrum of pathogens. The present research project is designed to study the binding of fish mucus isolated from common carp with silver nanoparticles. The characterization was done through FTIR and UV visible spectrophotometer. The peak of mucus based silver nanoparticles was higher than that of crude mucus extract in UV-visible spectrum. The FTIR spectra showed different functional groups such as alkanes, alkyl halides and amines. The different biological activities like antimicrobial, antioxidant and antibiofilm potential of fish mucus based nanoparticles were checked. For some activities, mucus exhibited better results and for others mucus based silver nanoparticles had higher activities. Fish mucus of common carp (Cyprinus carpio) showed highest antibacterial activity against E. coli bacteria with inhibition zone of 21 mm in crude mucus case. Lowest antibacterial activity was found against the B.subtilis with inhibition zone of 9 mm. Biochemical analysis exhibited higher values of catalase activity (CAT), superoxide dismutase activity (SOD), peroxidase activity (POD) and total soluble protein (TSP) for mucus and lowest for free silver nanoparticles.